THE ROLE OF VOCABULARY IN LEARNING LANGUAGE - Hazratqulova Robiya; Meliboyeva Feruzabonu; Muxtorova Oʻgʻilxon (Western European Studies, 2024)
Vocabulary plays a critical role in language learning and proficiency, serving as a foundational element that influences communication, comprehension, and expression. This abstract explores the significance of vocabulary acquisition in language learning processes, highlighting its impact on language development, fluency, and overall linguistic competence. The abstract delves into the multifaceted aspects of vocabulary learning, including the importance of word recognition, retention strategies, contextual usage, and expanding vocabulary breadth and depth. Additionally, it examines the relationship between vocabulary knowledge and language skills such as speaking, reading, writing, and listening comprehension. The abstract concludes by emphasizing the essentiality of vocabulary in language acquisition and the strategies and approaches that can enhance vocabulary acquisition to promote effective language learning outcomes.
Keywords: vocabulary; proficiency; young learners; comprehension